2005
DOI: 10.1111/j.1365-2303.2005.00213.x
|View full text |Cite
|
Sign up to set email alerts
|

Galectin‐3 is not useful in thyroid FNA

Abstract: Galectin-3 immunohistochemistry does not appear to be a useful adjunct to diagnosis in thyroid FNA as it does not reliably distinguish malignant and benign lesions. Many thyroid aspirates are of low cellularity and are not suitable for cell block immunohistochemistry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
31
1

Year Published

2006
2006
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(33 citation statements)
references
References 24 publications
1
31
1
Order By: Relevance
“…Therefore, Gal-3 protein might be an additional and valuable molecular tool not only to augment the diagnosis of malignant intra-prostatic disease but to also determine the biological activity with regard to the intra-cellular localization of the protein [5]. The observation that already benign glands in the neighborhood of the primary solid tumors as well as PIN lesions tissues exhibit a staining pattern that is substantially different from that in prostate specimens obtained from patients with benign prostatic disease might help to differentiate more precisely between benign and malignant biopsies as supposed for small needle biopsies from thyroid cancer [20][21][22].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, Gal-3 protein might be an additional and valuable molecular tool not only to augment the diagnosis of malignant intra-prostatic disease but to also determine the biological activity with regard to the intra-cellular localization of the protein [5]. The observation that already benign glands in the neighborhood of the primary solid tumors as well as PIN lesions tissues exhibit a staining pattern that is substantially different from that in prostate specimens obtained from patients with benign prostatic disease might help to differentiate more precisely between benign and malignant biopsies as supposed for small needle biopsies from thyroid cancer [20][21][22].…”
Section: Discussionmentioning
confidence: 99%
“…Although many reports have been published on this issue during the last decade (about 100 papers are displayed in Pub Med since 1997) some authors experienced conflicting results with the use of galectin-3 for improving diagnosis of follicular thyroid proliferations (Martins et al, 2002;Niedziela et al, 2002;Feilchenfeldt et al, 2003;JakubiakWielganowicz et al, 2003;De-Leon-Mazariegos et al, 2004;Mehrotra et al, 2004;Mills et al, 2005). However, some of these reports show major methodological problems (Herrmann et al, 2002;Bartolazzi et al, 2003;Bartolazzi and Bussolati, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…If it is true that FNA-derived cellular specimens are obtained and handled more easily and cheaply than LNAB-derived small tissue fragments, it should be mentioned that the occurrence of inadequate cytological specimens is higher with FNA than with LNAB preparations obtained with 20-gauge needle (Carpi et al, 1996(Carpi et al, , 1998. It has been recently reported that about 23% of thyroid aspirates have a low cellularity and are not suitable for cell-block preparation and galectin-3 immunostaining (Mills et al, 2005). In our experience, LNAB performed with 20-gauge needle retrieves much more tissue than FNA to be processed as paraffin-embedded cell block (Gasbarri et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, Shi et al and Yang et al have shown that if AUS cases are forced into either lower or higher diagnostic risk categories, the latter results in diminished sensitivity for detecting thyroid neoplasms, with increased false-negative and false-positive rates, making thyroid FNA a less effective screening test. 31,47 Future Directions Although to our knowledge immunohistochemistry has only a very limited role in thyroid cytology, [48][49][50] molecular testing using markers such as BRAF, RET/PTC, RAS, and paired box gene (PAX)/peroxisome proliferator-activated receptor-c (PPAR-c) shows more promise for wider applicability. [51][52][53][54] A BRAF mutation or RET/PTC gene rearrangement has very high specificity for PTC.…”
Section: Why Use the Aus/flus Category?mentioning
confidence: 99%